2020
DOI: 10.9734/jabb/2020/v23i230141
|View full text |Cite
|
Sign up to set email alerts
|

Nephropathic Changes in Renal Parenchyma of Wistar Rats Following Sub-chronic Exposure to Methanol Extract of Caladium bicolor (Aiton)

Abstract: To assess nephropathic potential of Caladium bicolor methanolic extract within the renal parenchyma of experimental Wistar rats. Twenty four albino Wistar rats (weighing between 180-195 g) were divided into four groups which include Group I treated with distilled water (2 ml/kg b.w.), Group II treated with methanolic extract of C. bicolor (100 ml/kg b.w.), Group III treated with methanolic extract of C. bicolor (200 ml/kg b.w.), Group IV treated with methanolic extract of C. bicolor (300 ml/kg b.w.). All admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…Accordingly, pathological changes in gastric and intestinal tissues of experimental animals following exposure to methanolic leaf extract of C. bicolor as observed in this study can be associated with toxic effects of its constituent phytochemicals particularly the calcium oxalate. The findings of this study were in consonance with results obtained from studies by Omotoso et al [20] and Akhigbemen et al [35] wherein the findings of their study showed that exposure to C. bicolor extracts induces deleterious effects on tissues of experimental animals. Also, in affirmation of findings by Nasri and Shirzad [36] about medicinal plants, C. bicolor can potently exert toxic effects characterized by variable tissue pathologies when its application is prolonged and not regulated.…”
Section: Effect Of Methanolic Leaf Extract Of C Bicolor On Histomorpsupporting
confidence: 93%
See 2 more Smart Citations
“…Accordingly, pathological changes in gastric and intestinal tissues of experimental animals following exposure to methanolic leaf extract of C. bicolor as observed in this study can be associated with toxic effects of its constituent phytochemicals particularly the calcium oxalate. The findings of this study were in consonance with results obtained from studies by Omotoso et al [20] and Akhigbemen et al [35] wherein the findings of their study showed that exposure to C. bicolor extracts induces deleterious effects on tissues of experimental animals. Also, in affirmation of findings by Nasri and Shirzad [36] about medicinal plants, C. bicolor can potently exert toxic effects characterized by variable tissue pathologies when its application is prolonged and not regulated.…”
Section: Effect Of Methanolic Leaf Extract Of C Bicolor On Histomorpsupporting
confidence: 93%
“…while the TGs I, II and III were administered with 100 ml/kg, 200 ml/kg and 300 ml/kg (b.w.) of methanolic leaf extract of C. bicolor respectively based on a previous study [20]. Administrations of reagent and extract were done orally and once daily for a period of thirty days with the aid of orogastric canula coupled to hypodermic syringe.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic properties of C. bicolor can be attributed to the presence of secondary metabolites such as tannins, alkaloids and saponins [30]. However, phytochemical analysis of C. bicolor also showed the presence of toxic calcium oxalate which has been implicated in pathology of internal organs such as the gastrointestinal tract and kidney [31,32]. This study was therefore carried out to assess probable pathological effect of sub-acute exposure of methanol extract of C. bicolor on hepatic histomorphology of experimental Wistar rats.…”
Section: Introductionmentioning
confidence: 99%